Building an Android application for Microsoft Imagine Cup 2015 - Quek, Benjamin Jia Wei (2015)
In this globalized society, everyone owns a smartphone and it plays an important role in his or her life. With high-speed network, information and news are at his or her fingertips. Even though, Apple owns a large market in smartphones sale, android phones are catching up in terms of market shares as the next leader in smartphones. As such, Android market is a good platform to develop applications for the greater good of people. This final year project’s objective is to develop an Android application to help the needy. The objective is to make use of the connectivity of this world to bring charity organisations, or donors and the needy closer. The main idea of this application is to allow donors to donate their unwanted items and upload onto the database for the charity groups to collect the items and distribute to the needy that needs it most. This project is done in a group of 3 under the supervision of Dr Tan Chee Wah Wesley. Each of the group members has different tasks, namely developing Android application, Windows Phone application and lastly, Web application and Server. The Android application covers two main aspects. The first aspect is to allow users to log in as well as to submit a donation through the application. The second aspect is to view the “Wishlist”, which are requests given from the needy to the charity groups. The outcome of this project is, as this is a first application of its kind in Singapore; it is a good initiative to bridge the gap between donors and the needy. In a way, it improves both parties’ lives as the donor, would feel appreciated from the donations and the needy people would feel that there are people who actually care for them despite their background.